2024
DOI: 10.1080/19490976.2023.2300846
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome-derived butyrate inhibits the immunosuppressive factors PD-L1 and IL-10 in tumor-associated macrophages in gastric cancer

Seung Yoon Lee,
JooYeon Jhun,
Jin Seok Woo
et al.

Abstract: Early detection and surgical treatment are essential to achieve a good outcome in gastric cancer (GC). Stage IV and recurrent GC have a poor prognosis. Therefore, new treatments for GC are needed. We investigated the intestinal microbiome of GC patients and attempted to reverse the immunosuppression of the immune and cancer cells of GC patients through the modulation of microbiome metabolites. We evaluated the levels of programmed death-ligand 1 (PD-L1) and interleukin (IL)-10 in the peripheral blood immunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Although direct research linking Rothia with gastric cancer is limited, it is important to note that Rothia is part of the core microbiota in the stomachs of healthy individuals ( Nardone and Compare, 2015 ). The gut microbiota can produce butyrate, a short-chain fatty acid that has been shown to suppress the expression of PD-L1 and IL-10 in immune cells and demonstrate tumor growth inhibition potential in mouse models ( Lee et al, 2024 ). It is speculated that Rothia may influence the progression of gastric cancer through its metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct research linking Rothia with gastric cancer is limited, it is important to note that Rothia is part of the core microbiota in the stomachs of healthy individuals ( Nardone and Compare, 2015 ). The gut microbiota can produce butyrate, a short-chain fatty acid that has been shown to suppress the expression of PD-L1 and IL-10 in immune cells and demonstrate tumor growth inhibition potential in mouse models ( Lee et al, 2024 ). It is speculated that Rothia may influence the progression of gastric cancer through its metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…Although much remains to be elucidated, there is evidence for individual metabolites acting to either improve responses to cancer therapy, such as indole-3-acetic acid ( 85 ), or mitigate against high-fat-diet-mediated progression of intestinal tumors, such as butyrate ( 86 ). Moreover, butyrate was shown to inhibit gastric tumors by reducing the expression of immunosuppressive factors, such as PD-L1 and IL-10 ( 87 ). In the context of colorectal cancer, a recent study demonstrated that oral administration of Lactobacillus plantarum CBT could effectively inhibit the growth of colorectal cancer in noth orthotopic as well as ectopic preclinical mouse models ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…68 Butyrate also decreases the levels of immunosuppressive PD-L1 and interleukin (IL)-10 in tumour-associated macrophages, thereby restraining GC tumour growth (figure 2). 64…”
Section: Mechanistic Links Between Beneficial Bacteria and Gcmentioning
confidence: 99%
“…For example, microbes-derived butyrate suppresses the expression of PD-L1 and IL-10 in tumour-associated macrophages in mouse models of GC. 64 Butyrate could also enhance the function of CD8 + T cells in the microenvironment of GC through GPR109A/HOPX pathway (figure 2). 68 Nevertheless, it is important to pinpoint that the role of microbes in immunotherapy for GC, especially at cellular and molecular levels, remains massively unclear.…”
Section: Beneficial Bacteria In Gc Treatmentmentioning
confidence: 99%